Development and evaluation of tools and an intervention to improve patient- and carer-centred outcomes in Longer-Term Stroke care and exploration of adjustment post stroke: the LoTS care research programme - Anne Forster; Kirste Mellish; Amanda Farrin; Bipin Bhakta; Allan House; Jenny Hewison; Jenni Murray; Anita Patel; Martin Knapp; Rachel Breen; Katie Chapman; Ivana Holloway; et al. (Programme Grants for Applied Research, 2014)
Background: Evidence-based care pathways are required to support stroke patients and their carers in the longer term. Aims: The twofold aim of this programme of four interlinking projects was to enhance the care of stroke survivors and their carers in the first year after stroke and gain insights into the process of adjustment. Methods and results: We updated and further refined a purposely developed system of care (project 1) predicated on a patient-centred structured assessment designed to address areas of importance to patients and carers. The structured assessment is linked to evidence-based treatment algorithms, which we updated using a structured protocol: reviewing available guidelines, Cochrane reviews and randomised trials. A pragmatic cluster randomised controlled trial evaluation of the clinical effectiveness and cost-effectiveness of this system of care was undertaken in 29 community-based UK stroke care co-ordinator services (project 2). In total, 15 services provided the system of care and 14 continued with usual practice. The primary objective was to determine whether the intervention improved patient psychological outcomes (General Health Questionnaire-12) at 6 months; secondary objectives included functional outcomes for patients, outcomes for carers and cost-effectiveness, as measured through self-completed postal questionnaires at 6 and 12 months. A total of 800 patients and 208 carers were recruited; numbers of participants and their baseline characteristics were well balanced between intervention and control services. There was no evidence of statistically significant differences in primary or secondary end points or adverse events between the two groups, nor evidence of cost-effectiveness. Intervention compliance was high, indicating that this is an appropriate approach to implement evidence into clinical practice. A 22-item Longer-term Unmet Needs after Stroke (LUNS) questionnaire was developed and robustly tested (project 3). A pack including the LUNS questionnaire and outcome assessments of mood and social activity was posted to participants 3 or 6 months after stroke to assess acceptability and validity. The LUNS questionnaire was re-sent 1 week after return of the first pack to assess test–retest reliability. In total, 850 patients were recruited and the acceptability, validity and test–retest reliability of the LUNS questionnaire as a screening tool for post-stroke unmet need were confirmed. This tool is now available for clinical use. An in-depth qualitative investigation was undertaken with 22 patients (and carers) at least 1 year after stroke (project 4) to gain further insights into the experience of adjustment. This included initial semistructured interviews, limited observations and solicited diaries with a follow-up interview 3–4 months after the initial interview and highlighted a range of different trajectories for post-stroke recovery. Conclusions: The programme has been completed as planned, including one of the largest ever stroke rehabilitation trials. This work highlights that successfully addressing the needs of a heterogeneous post-stroke population remains problematic. Future work could explore stratifying patients and targeting services towards patients (and carers) with specific needs, leading to a more specialised bespoke service. The newly developed LUNS questionnaire and the qualitative work will help inform such services. Trial registration: Current Controlled Trials ISRCTN67932305. Funding: The National Institute for Health Research (NIHR) Programme Grants for Applied Research programme. The Bradford Teaching Hospitals NHS Foundation Trust received additional funding for project 2 in the submitted work from the Stroke Association, reference number TSA 2006/15. The initial development work for the LUNS tool and the Longer-Term Stroke care (LoTS care) trial carried out before the start of the programme grant was funded by the Stroke Association, reference number TSADRC 2006/01.